Role of Supply Chain Management on the Job Control and Social Support for Relationship between Work-Family Conflict and Job Satisfaction - R Zirwatul Aida R Ibrahim; Jumadil Saputra; Azlina Abu Bakar; Mazidah Mohd Dagang; Siti Nazilah Mat Ali; Md Aris Safree Md Yasin (International Journal of Supply Chain Management, 2019)
Abstract- The present study investigates the relationship between work-family conflict and job satisfaction of Malaysian workers (N = 1125) based on the supply chain management. It examines the direct and moderating effects of job control and social support on work-family conflict and job satisfaction relationship. The current study examines the Job Demand-Control (JDC) [1] and Job Demand-Control-Support (JDCS) [2] models which are under research in the work-family conflict. Hierarchical regression analyses in the study reveal that work to family conflict (WFC), family to work conflict (FWC) and social support have a direct effect on job satisfaction. However, the result reveals that employees’ job control was not the primary predictor of their job satisfaction. Contrary to the prediction of the JDCS model, the moderating effects of job control and social support on the relationship between work-family conflict and job satisfaction are not found. Implications regarding the importance of the main effect of social support and supply chain management on understanding job satisfaction in Malaysian society and other possible moderators are discussed.